ICT-Based Identification and Characterisation of Small Reservoirs in the Limpopo River Basin in Zimbabwe - Mulengera, Patrick-M. Bahal’okwibale; Manzungu, Emmanuel; Kileshye Onema, Jean-Marie (Canadian Center of Science and Education, 2012)
Semi-arid conditions that prevail in the Limpopo basin in general and Zimbabwe in particular emphasise the importance of water storage. In this respect small reservoirs play a critical role in sustaining rural livelihoods. However, the management of small reservoirs in Zimbabwe is negatively affected by missing or poorly coordinated information relating to such key attributes as location, capacity, and environmental condition. A study was undertaken to identify and characterise small reservoirs in the Limpopo river basin in Zimbabwe. The objective of the study was to identify small reservoirs and characterise them in terms of capacity, and chlorophyll-a and turbidity indices, as proxies for measuring environmental degradation of catchments in which these are located. The study was carried out in Gwanda district that is located in South West Zimbabwe. Identification was done by processing Landsat TM 4-5 images of February-March and April-May 2009, using Geographical Information Systems. Time and cost considerations were the main factors in the selection of the technology and the images that were used. Field inspections were used to validate selected parameters from February to April 2011. A total of 256 small reservoirs, with an estimated total capacity of 17 million m3, were identified. The capacities of reservoirs were found to vary widely from around 4,000 m3 to over 650,000 m3. About half (46%) of the small reservoirs were found to be dry by May, just two months after the end of the wet season. Seven reservoirs, which represented 2% of the total number and 3% of the total capacity of reservoirs, were characterised as highly turbid. Twenty-three reservoirs, representing 9% of the total number and 3% of the total capacity of reservoirs, showed signs of environmental degradation in the catchments. The smallest reservoirs were found to be most vulnerable to environmental degradation. The study concluded that Information and Communication Technologies (ICTs) can successfully be used to identify and characterise small reservoirs in the data-poor Limpopo basin in Zimbabwe, and can be used by decentralised water institutions and River Basin Organisations (RBOs) to better manage available water resources for the benefit of rural communities found therein.